Treatment-related transient splenial lesion of the Corpus Callosum in patients with neuropsychiatric disorders: a literature overview with a case report. Issue 3 (3rd March 2020) - Cirnigliaro, Giovanna; Di Bernardo, Ilaria; Caricasole, Valentina; Piccoli, Eleonora; Scaramelli, Barbara; Pomati, Simone; Villa, Chiara; Pantoni, Leonardo; Dell'Osso, Bernardo
ABSTRACT: Introduction : Transient-localized lesions of the splenium of the corpus callosum (SCC) have been described in various clinical conditions, some of them being attributed to the withdrawal of psychotropic drugs. The pathophysiology of the lesion reflects cytotoxic edema and reversible demyelination. Areas covered : The present article aimed at reviewing cases of transient SCC lesion exclusively related to changes in pharmacotherapy. It also reports the original case of a patient receiving a complex psychopharmacological therapy who developed a transient SCC lesion investigated by magnetic resonance imaging (MRI), magnetic resonance spectroscopy (MRS), and pharmacogenetic profiling. Expert opinion : To date, only one review on the subject has been published, analyzing 22 cases of transient SCC lesion arising in epileptic patients on antiepileptic therapy. It hypothesized that the nature of the lesion is a cytotoxic edema and the cases described in the subsequent 14 years seem to support this hypothesis. The authors reported the case of an Italian-Egyptian patient who developed a transient SCC lesion after the rapid withdrawal of Carbamazepine and Lurasidone. The lesion completely disappeared from the MRI performed after 1 month. Patient's ethnic group and its pharmacogenetic profile were considered as possible causes of altered drug metabolism and, likely, of the SCC lesion.